DIRECTIONS OF CROSS-CULTURAL COMMUNICATIONS DEVELOPMENT IN THE CONDITIONS OF CHANGES IN THE BUSINESS ENVIRONMENT AND BUILDING THE POTENTIAL OF KNOWLEDGE MANAGEMENT - Фінагіна, Олеся; Павловська, Анна; Горохова, Людмила; Пригодюк, Олена (SWorldJournal, 2022)
Features of formation of modern international business relations, improvement of cross-cultural communications in the directions of business environment development with priorities of the accumulated potential of knowledge management involvement are consi